Ethnosains dalam pembelajaran berbasis content local genius (Gamelan Bali) - Ketut Sri Kusuma Wardani (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Ethnoscience is a science learning technique that uses cultural goods to teach local wisdom (regional culture) as an object of study. Based on local genius material, this study aims to classify artifacts and scientific activities that can be found in science learning (gamelan bali). Observation and curriculum analysis activities in grade IV SD Negeri 34 Cakranegara provided the research results. First, the Balinese gamelan instruments (gong/kempur, gangsa, ceng ceng, kendang, rindik, tektekan, kul-kul, suling) were studied. Second, the sensory material of listening, vibrations, waves, sounds, resonances, sound propagation, sound reflection, and the sonar system are IPA artifacts that can be recognized, and their use is linked to local genius content (Balinese gamelan). Third, science learning activities such as studying and recognizing science objects, searching for patterns of relationships with local community activities, and providing student worksheets are available.Etnosains merupakan suatu pendekatan pembelajaran IPA yang mengimplementasikan kearifan lokal (budaya daerah) tertentu sebagai objek pembelajan menggunakan produk budaya tertentu. Penelitan ini bertujuan untuk mengidentifikasi objek dan aktivitas sains yang dapat ditemukan pada pembelajaran IPA berbasis content local genius (gamelan bali). Data penelitian didapatkan melalui kegiatan observasi dan kajian kurikulum pada siswa kelas IV SD Negeri 34 Cakranegara. Hasil penelitian adalah Pertama, alat kesenian gamelan bali (gong/kempur, gangsa, ceng ceng, kendang, rindik, tektekan, kul-kul, suling). Kedua, objek IPA yang dapat diidentifkasi adalah materi indera pendengaran, getaran, gelombang, bunyi, resonansi, cepat rambat bunyi, pemantulan bunyi, serta sistem sonar dan pemanfaatannya berkaitan dengan content local genius (gamelan bali). Ketiga, aktivitas belajar IPA yang dapat dilakukan dengan mengamati dan mengidentifikasi objek IPA, mencari pola hubungan dengan aktivitas masyarakat setempat, dan presentasi hasil lembar kerja siswa.